The profit rate: where and how much did it fall? Did it recover? (USA 1948-2000) - Dumenil, Gerard; Levy, Dominique (2002)
The decline of the profit rate since World War II, up to the early 1980s, is now widely acknowledged, and a new upward trend has been identified. This study presents new computations of profits using a definition like that used by Marx in Volume III of Capital, where profits correspond to total surplus-value, as well as a definition of the rate of profit that impacts individual firms, taking account of interest, taxes, and inventories. We show that both the level and trend of a specific group of industries (such as Railroads), called Highly Capital Intensive Industries, whose capital - labor ratio is very large, are totally different from that of other industries. (Their profit rate is very low and did not decline.) When these industries are removed from the data set, the downward trend of the profit rate and the limited recovery can be more clearly observed. Overall, between 1948 and 1982, the profit rate was divided by a coefficient ranging between 2 and 7, depending on the sector and definition of the profit rate. The profit rate in 2000 is still only half of its value i 1948. Finally, we show that the decline of the productivity of capital was the main factor in the fall of the profit rate, though the decline of the share of profits also contributed to this evolution. - Reproduced.
Keywords: Profits - United States; Profits